Hyperuricemia Is Associated With the Risk of Atrial Fibrillation Independent of Sex: A Dose-Response Meta-Analysis - Xiong, Jianhua; Shao, Wen; Yu, Peng; Ma, Jianyong; Liu, Menglu; Huang, Shan; Liu, Xiao; Mei, Kaibo (Frontiers in Cardiovascular Medicine, 2022)
Background: The sex-specific associations between serum uric acid (SUA) and the risk of atrial fibrillation (AF) are unclear, although hyperuricemia is independently associated with the risk of AF. Methods: The PubMed, EMBASE, and Cochrane Library databases were searched up to October 3, 2021 for studies that reported sex-specific associations of SUA concentration levels with AF. This study was registered with PROSPERO (42020193013). Results: Ten eligible studies with 814,804 participants (415,779 men and 399,025 women) were identified. In the category analysis, high SUA was associated with an increased risk of AF in both men (OR: 1.42; 95% CI, 1.18–1.71, I2=34%) and women (OR: 2.02; 95% CI, 1.29-3.16, I2=70%). In the dose-response analysis, for each 60 µmol/L (1 mg/dL) increase in the SUA concentration level, the risk of AF increased by 15% (OR: 1.15; 95% CI, 1.07–1.25, I2=74%) in men and 35% (OR: 1.35; 95% CI, 1.18–1.53, I2=73%) in women. There was a borderline difference in the impact of SUA on the risk of AF between men and women (P for interaction=0.05). A significant linear relationship between SUA and the risk of AF was observed in men (P for nonlinearity=0.91) and women (P for nonlinearity=0.92). Conclusions: This study suggested that there was a significant linear relationship between SUA and the risk of AF among men and women, with a higher risk estimate for women. Additional trials are required to assess the effect of reduced SUA therapy on AF incidence.